Peran Kepala Sekolah Dalam Manajemen Peningkatan Mutu Lembaga Pendidikan: Studi Deskriptif di SMA Negeri 1 Kroya Kabupaten Cilacap - Agus Prayitno; Reni Wahyuningsih; Nurfuadi Nurfuadi (Universitas Islam Bunga Bangsa Cirebon, 2020)
In an educational institution the principal has a very important role in determining the back and forth of an educational institution because the principal is one of the components of education that has the most role in improving the quality of education and is directly responsible for education management which is directly related to all processes in a school. The principal has a big role in the process of improving the management of educational institutions, one of which is the principal as the top leader who has the right to make decisions and gives authority to teachers and all school members, the principal also supervises and monitors all matters relating to the school in particular and educational institutions in general. The purpose of this research was to determine the role of the principal in the quality management of educational institutions at SMA Negeri 1 Kroya, Cilacap Regency. The research that the authors do is included in the type of qualitative research. In collecting data, the author uses the method of observation, interviews, and documentation. From the research results, the data are collected and analyzed, then the data is reduced, then the data is presented in descriptive form and drawing conclusions. The results showed that the role of the principal in the management of quality improvement of educational institutions at SMA Negeri 1 Kroya is realized in the form of activities related to program achievement and school policy. In the management of improving the quality of educational institutions at SMA Negeri 1 Kroya, 4 stages are carried out according to the